2015
DOI: 10.1007/s00436-015-4397-z
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of fipronil combined with permethrin commercial spot on (Effitix®) preventing Culex pipiens from feeding on dogs

Abstract: A controlled clinical trial was carried out to assess the adulticidal and anti-feeding effectiveness of a spot-on combining fipronil and permethrin (Effitix®, Virbac, Carros, France) in preventing Culex pipiens from feeding on dogs. Twelve dogs with equal sensitivity to mosquitoes were included in the study and divided into two groups of six dogs: an untreated control group and a group treated with Effitix®. All dogs were challenged with 80 females C. pipiens for 90 ± 5 min on days −7, 1, 7, 14, 21, and 28 (da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 31 publications
0
6
0
Order By: Relevance
“…Recent studies reported the efficacy of other combinations containing permethrin combined with fipronil (Effitix®, Frontline Tri-Act®/Frontect®) on the same target, Culex pipiens ( Fankhauser et al, 2015 , Franc et al, 2015 ). The feeding inhibition provided by Vectra® 3D was similar or even better to the one obtained with these both new spot-on formulations containing approximately the same dose of permethrin.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recent studies reported the efficacy of other combinations containing permethrin combined with fipronil (Effitix®, Frontline Tri-Act®/Frontect®) on the same target, Culex pipiens ( Fankhauser et al, 2015 , Franc et al, 2015 ). The feeding inhibition provided by Vectra® 3D was similar or even better to the one obtained with these both new spot-on formulations containing approximately the same dose of permethrin.…”
Section: Discussionmentioning
confidence: 99%
“…The feeding inhibition provided by Vectra® 3D was similar or even better to the one obtained with these both new spot-on formulations containing approximately the same dose of permethrin. The repellency of Effitix® against C. pipiens was 100% (Day 1), 99.5% (Day 7), 97.7% (Day 14), 98.3% (Day 21) and 96.7% (Day 28) ( Franc et al, 2015 ) while the efficacy of Frontline Tri-Act®/Frontect® was a bit lower with 99.4% (Day 1), 98.9% (Day 7), 94.7% (Day 14), 91.7% (Day 21) and 90.4% (Day 28) ( Fankhauser et al, 2015 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The product is licensed in dogs to be used against infestations with fleas and/or ticks and when repellent activity is also necessary against sand-flies and/or mosquitoes. The product has a persistent insecticidal/acaricidal efficacy for up to 4 weeks against fleas [15], ticks [16,17], sandflies [18], and mosquitoes [19]. Very recently, the product was successfully evaluated on adult triatomines (Rhodnius prolixus) in dogs [20].…”
Section: Discussionmentioning
confidence: 99%
“…Several approved compounds of macrocyclic lactones (e.g., ivermectin, milbemycin oxime, moxidectin, and selamectin) administrated alone or in combination with other parasiticides are available for oral administration or topical application [3]. Finally, external repellent antiparasitic agents containing synthetic pyrethroids, deltamethrin, or permethrin are particularly suitable for the control of vectors of dirofilariosis (a repellent effect against mosquitoes) and their efficacy has been demonstrated both experimentally and in field studies [65-67]. One of them, based on a dinotefuran-permethrin-pyriproxyfen combination has recently demonstrated its effectiveness in the prevention of canine dirofilariosis in combination with a macrocyclic lactone [68].…”
Section: Dirofilariosismentioning
confidence: 99%